Adaptógenos: plantas medicinales tradicionales comercializadas como suplementos dietéticos en la conurbación Buenos Aires-La Plata (Argentina) - Arenas, Patricia Marta (2011)
This paper presents the results of a study on three species, of which commercialize products considered adaptogens: Lepidium meyenii Walp. (Brassicaceae), “maca”, Morinda citrifolia L.(Rubiaceae), “noni”, and Petiveria alliacea L. (Phytolaccaceae), “pipi”. The data come from an Urban Ethnobotany study conducted in Buenos Aires-La Plata conurbation. The traditional uses of the species, their access routes, marketing and diffusion as dietary supplements in urban pluricultural context are presented, as well as current modes of use and related knowledge which are part of local botanical knowledge. Thus, modifications in the uses originally assigned as result of the expansion of the products in the context of globalization are evaluated, well as the consequent changes in traditional patterns of knowledge, beliefs and practices related to these plant resources.